TI_GERICHTE 12.2020.107 vom 1. Februar 2021 , Responsabilità per atto illecito - responsabilità del proprietario dell'opera - TI Tribunale d'appello (2021)
Responsabilità per atto illecito - responsabilità del proprietario dell'opera